Ananalysis Of The Students’ Error In Writing Descriptive Text - Diani Syahputri; Siti Masita (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2018)
This study deals with an analysis on students’ errors in writing Decsriptive text. The objectives of this study were to find out the kinds of error made by students in writing descriptive text, and to find out the most dominant kinds of error made by students in writing descriptive text. This study was conducted at SMP SWASTA BUDI SETIA SUNGGAL with the number of population was 175 students of eight grade students. They were into five classes. By using random sampling was conducted to take the sample of research. The total sample was 35 students of eight grade students. Written test as the instrument was used in this research. The method of the research was descriptive quantitative method. The research of this study is only one week. The result of the test showed that there were four types of error in writing. They were omission, addition, misformation and misordering. The dominant types of error in writing descriptive text was omission with 86 or 43% error, then misformation with 45 or 22.5%. Next misordering error with 39 or 19.5%. And the last addition error with 30 or 15%. The cause of error found in students” writing text, they were intralingual interference, interlingual interference and carelessness.Key Word :Error Analysis,Writing,Descriptive Text,